RETRACTED: Rethinking sustainable energy development for green energy recovery: Empirical dynamism of oil prices shock - Leng, Feng (Frontiers in Energy Research, 2022)
The purpose of the study is to test the role of market timing between oil prices shock and energy efficiency mitigation in ASEAN countries. To achieve the study objective, a persistence econometric modelling technique is applied. The results revealed that oil prices are now the another main source of energy efficiency mitigation in ASEAN economies. Market timing based factors are replaced with for oil prices shock to raise, warranting collaborative environment. Moreover, green financing loan schemes invest both public and private funds in energy efficiency mitigation to capitalize a cleaner environment by controlling the oil prices shock. The consideration and application of financial consideration for sustainable innovation-financing projects or companies is limitless. Providing for screening CO2 emission reduction and cooperation proposals with speedy greenhouses gasses reduction rates might have large opportunity costs. There may be a case for governments to increase industrial growth, improve resource efficiency and increase factor productivity while tackling energy efficiency. Economic growth in ASEAN may have an even greater influence on greenhouse gasses reduction than in other countries. On such points there is a need to pay the attention. If the suggested policy suggestions are implemented successfully, they would help to enhance the scope of financing considerations for sustainable innovation to uplift energy efficiency mitigation through market timing based mechanisms.